The completed SDSS-IV extended baryon oscillation spectroscopic survey: pairwise-inverse probability and angular correction for fibre collisions in clustering measurements. Issue 1 (11th August 2020) - Mohammad, Faizan G; Percival, Will J; Seo, Hee-Jong; Chapman, Michael J; Bianchi, D; Ross, Ashley J; Zhao, Cheng; Lang, Dustin; Bautista, Julian; Brinkmann, Jonathan; Brownstein, Joel R; Burtin, Etienne; et al.
ABSTRACT: The completed extended Baryon Oscillation Spectroscopic Survey (eBOSS) catalogues contain redshifts of 344 080 quasars at 0.8 < z < 2.2, 174 816 luminous red galaxies between 0.6 < z < 1.0, and 173 736 emission-line galaxies over 0.6 < z < 1.1 in order to constrain the expansion history of the Universe and the growth rate of structure through clustering measurements. Mechanical limitations of the fibre-fed spectrograph on the Sloan telescope prevent two fibres being placed closer than 62 arcsec in a single pass of the instrument. These 'fibre collisions' strongly correlate with the intrinsic clustering of targets and can bias measurements of the two-point correlation function resulting in a systematic error on the inferred values of the cosmological parameters. We combine the new techniques of pairwise-inverse probability and the angular upweighting (PIP+ANG) to correct the clustering measurements for the effect of fibre collisions. Using mock catalogues, we show that our corrections provide unbiased measurements, within data precision, of both the projected w_p( r_p) and the redshift-space multipole ξ (ℓ = 0, 2, 4) ( s ) correlation functions down to 0.1 h^-1Mpc, regardless of the tracer type. We apply the corrections to the eBOSS DR16 catalogues. We find that, on scales s20 h^-1Mpc for ξ ℓ, as used to make baryon acoustic oscillation and large-scale redshift-space distortion measurements, approximate methods such as nearest-neighbour upweighting are sufficiently accurate given the statistical errors of the data. Using the PIP method, for the first time for a spectroscopic program of the Sloan Digital Sky Survey, we are able to successfully access the one-halo term in the clustering measurements down to 0.1 h^-1Mpc scales. Our results will therefore allow studies that use the small-scale clustering to strengthen the constraints on both cosmological parameters and the halo occupation distribution models.